The fundamentals ; v. 3 a testimony to truth (Los Angeles, CA The Bible Institute of Los Angeles, 1917)
Some articles include bibliographical references.
Originally published in 12 volumes. Sir Robert Anderson, 1841-1918 (author of chapter 4), Brethren writer.
Keywords: Doctrine, theology